Influência do uso de líquidos modeladores na estabilidade cromática de resinas compostas - Chaves, Eduardo Trota (2021)
Modeling resins and dental adhesives are proposed as agents that facilitate the manipulation of composite resins. However, the possible effects on the chromatic stability of composite resins still represent a gap to be explored, considering their wide clinical use. This In Vitro study aimed to evaluate the color stability and the influence of different modeling liquids on four commercial brands of composite resins. Eighty specimens were distributed based on the combination of one of the composite resins: IPS Empress Direct; Diamond Charisma; Filtek Z350XT and Forma, modeled with modeling liquids: Wetting Resin, Modeling Resin, Ambar APS Adhesive or a control group (without modeler application). Each group had five specimens. (n = 5) and were evaluated chromatically, with the aid of a spectrophotometer (SP60, X-Rite) in the periods: T0 (immediate), T1 (30 days), T2 (4 months) and T3 (6 months). The specimens were aged in deionized water at controlled temperature. From the measurement of chromatic coordinates L *, a * and b *, the results were evaluated using the CIEDE2000 system equation. The results were subjected to analysis of variance (ANOVA) and Bonferroni’s post-hoc test, considering significance levels of 5% and interpreted in terms of perceptibility, acceptability and individual evaluation of chromatic coordinates. No statistical significance was found in the choice of the modeler (p = 0.31) or in the triple modeler / resin / time interaction (p = 0.92). However, the composite resin and the reading times were statistically significant (both p <0.00). An increase to the values of ΔΕ00 was noted when (T0-T1) was confronted with (T0-T2). In contrast, at the end of 180 days (T0-T3), the specimens seem to achieve chromatic stability, either due to their reduction or equity to the values due in the previous period (T0-T2). According to the interpretation parameters, at the end of 180 days, the IPS Empress and Z350XT composite resins have similar good interactions with the modelers, a Forma resin shows the best behavior with the Ambar modeler and the Charisma resin presents acceptable results when modeled with the model. Watering liquid. The control groups of all resins evaluate values for ΔΕ00 higher than those considered acceptable by the study. Values refer to a variation ranging from 0.50 (Z350 + Humidification T0-T1) to 3.26 (Charisma + Ambar T0-T3). The individual evaluation of the coordinates L *, a * and b * allows to visualize, in general, a reduction in the luminosity of the bodies (darkening), as well as an increase in blue hue (reduction of a *) and red hue (increase of b *). The use of modeling liquids has an influence on the chromatic stability of the resins. However, the color changes were more influenced by the choice of composite resin. Thus, according to the results and limitations of the study, some composite resins present acceptable results for chromatic stability, when combined with modeling liquids.